Building a better mobile app marketplace: A legal and governance toolkit for app mediated genomics research. Issue 46 (September 2022) - McKibbin, Kyle J; Shabani, Mahsa
Abstract: Due to ongoing developments in mobile health research and consumer genomics services, genomics mobile applications are set to become an increasingly important tool for biomedical researchers, offering to generate new insights into human health and shake up traditional research methods. However, as with other areas of mobile health research, current data governance and legal frameworks have failed to keep pace with these technological developments, generating ethical concerns and potential harms for research participants. Here, we explore the specific roles and responsibilities of the two major mobile platform providers, IOS and Android, in mediating genomics research on their platforms. This mobile platform duopoly and their respective app marketplaces play a significant role in the governance and design of app mediated research studies through the provision of technical infrastructure and contractual guidelines for developers. However, these platforms are not clearly regulated by the General Data Protection Regulation in this regard and are likely to have divergent and sometimes conflicting interests with researchers and research participants.  Two regulatory proposals, the Digital Services Act and Digital Markets Act, are set to introduce new obligations and oversight for mobile platforms. These laws are targeted more toward consumer protection and competition concerns, but they also offer new opportunities for promoting better data governance on platforms. Taking advantage of these legislative proposals, we offer a governance and legal toolkit for researchers, advocacy groups, national authorities, and platform providers interested in building a better app marketplace for genomics research.